THE IMPORTANCE OF WORK PLACE SAFETY - Riak PhD, Gabriel Alier; Bill, Dut Bol Ayuel (IJRDO - Journal of Social Science and Humanities Research, 2022)
Work place safety involves activities that are task oriented and is more than proactive selling of products and services through use of face-to-face interactions or by use of other communications means such as telephone or mail. The goal of customer satisfaction should be designed, communicated and performed with the aim of achieving two goals which are to satisfy the customer and to achieve operational efficiency. The behavior and interaction of the service provider with customers for services that are offered face to face is a replica of what goes on inside the organization (Lovelock, 2014). The marketing of financial services is not only more complex but also much broader and it involves increased interactions between the customer and the organization as the service is made, sold and also consumed. The customer’s view of the quality of the service is drawn from the behaviour and personality of the service provider. High quality customer service can be drawn from thinking, attitude and a philosophy that puts more emphasis on a way of doing business which is committed and sincerely dedicated to satisfy the firm’s customers. Such a philosophy emphasise that customer satisfaction is the greatest priority of the organization (Lovelock, 2014).